2023
DOI: 10.3390/microorganisms11020484
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Complex Gut Microbiomes Influence Fetal Growth, Food Intake, and Adult Body Weight in Outbred Mice

Abstract: Obesity places a tremendous burden on individual health and the healthcare system. The gut microbiome (GM) influences host metabolism and behaviors affecting body weight (BW) such as feeding. The GM of mice varies between suppliers and significantly influences BW. We sought to determine whether GM-associated differences in BW are associated with differences in intake, fecal energy loss, or fetal growth. Pair-housed mice colonized with a low or high microbial richness GM were weighed, and the total and BW-adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 49 publications
2
5
0
Order By: Relevance
“…Compositional differences between GM Low and GM High have been described previously 3234 , including greater richness in GM High compared to GM Low ( Fig. 2a ).…”
Section: Mainsupporting
confidence: 65%
See 1 more Smart Citation
“…Compositional differences between GM Low and GM High have been described previously 3234 , including greater richness in GM High compared to GM Low ( Fig. 2a ).…”
Section: Mainsupporting
confidence: 65%
“…Taxonomic differences are associated with different levels of biologically relevant metabolites Compositional differences between GM Low and GM High have been described previously [32][33][34] , including greater richness in GM High compared to GM Low (Fig. 2a).…”
Section: Complex Microbiome-dependent Behaviors Determined By Materna...supporting
confidence: 55%
“…The postnatal GM-mediated effects on body weight identified in this study were of particular interest. In CD-1 mice, we have historically found that animals with a Jackson-origin microbiome (GM Low ) are heavier than those with an Envigo-origin (GM High ), beginning in utero and persisting into adulthood 12,13 . The GM-dependent difference in body weight observed in CD-1 mice is likely due to an effect on overall growth, as these groups do not differ in relative body composition and GM Low CD-1 mice exhibit increased cardiac weight 12 .…”
Section: Discussionmentioning
confidence: 99%
“…While assessing the effect of supplier-origin GMs on the ASD-related behavior of BTBR mice, we collected body weights as previous work by our group using comparable GMs in CD-1 mice has revealed microbiome-dependent effects on body weight 12,13 . In the cohort of neonatal mice used for USV testing, we measured body weight at birth (D0) and after testing (D7).…”
Section: Standardized Complex Gms Postnatally Affect Body Weightmentioning
confidence: 99%
See 1 more Smart Citation